Impact of Blood Transfusion on Postoperative Infection and Hospital Stay after Isolated Coronary Artery Bypass Surgery - Goher Bashir, Ajwad Farogh, Muhammad Irfan Khan, Asma Hassan, Naseem Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The blood transfusion during cardiac surgeries has been demonstrated to be increased in length of hospital stay. The aim of current study was to characterize the post-operative complication. Methodology: A descriptive study was conducted at Cardiac Centre Bahawalpur from 1st February 2020 to 30th March, 2021 all patients were divided into two groups. who underwent cardiac surgery during this period Group A (No blood transfusion). Group B (low transfusion 1-2 units) Results: A total of 176 patients, 122 (69.3%) were male and 54 (30.7%) female. in our study there were 1(1%) in Group A while 5(6.6%) in Group B were found with post-operative infection with statistically significant p-value 0.049. Similarly, hospital stay in group A was 5.8 ± 1.3 while in Group B was 6.9 ± 0.3 showing insignificant p-value 0.067. Conclusion: A restrictive transfusion policy while considering RCC transfusion seems more useful and patients who require blood should receive the number of transfusions as minimum as possible. Keywords: RCC Red Cell Concentrates Transfusion, CABG Cardiac Artery Bypass Graft, LOH Length of Hospital Stay, restrictive blood transfusion.